THE IMPACT OF NURSE-LED CARE COORDINATION FOR PATIENTS WITH COMPLEX CONDITIONS - Halyma Abdullah Alymi, Albandry Abdulaziz Alnasser, Reham Senhat Alotaibi, Amany Modhaya Omair, Fatem Bhees Aswiny, Alaa Ali Safhi, Fatimah Ali Jari, Amal Ahmed Kumayt, Wafa Ali Hmoud Mashykhei,; Sami Hussain Almalki, Reem Azwi Khudhayr Alharbi, Abdullah Mabar Y Alribhi, Ameera Mabrook Allugmaine, Fatimah Mohammed Ahmad Alhazmi, Naïf Ghazi Alotaibi (Chelonian Research Foundation, 2022)
Patients with multimorbidity in hospital, owing to their intricate medical conditions, get advantages from a care management strategy headed by nurses. This care management strategy facilitates more accurate assessment of patients' needs and employs a person-centred approach. The objective of this scoping study is to delineate the nurse-led care management approaches for patients with multiple chronic conditions in hospital settings. This review adhered to the JBI approach for conducting scoping reviews. The search included the worldwide databases Web of Science, CINAHL, MEDLINE, Nursing & Allied Health Collection, as well as grey literature. The data revealed three distinct groups of nurse-led care management models: nurse-led programs, case management, and nurse facilitator models. The interventions were centered on training, providing assistance upon release, doing follow-up, promoting health, and delivering patient-centered care. A key feature of nurse-led care models is the emphasis on placing the patient at the center. This includes helping patients develop skills to manage their own diseases, preparing them for leaving the hospital, and ensuring a smooth transition of care in the community. Keywords: Review, patients, complex condition, nurse, nurse intervention, hospitals.